The gardens of desire : Marcel Proust and the fugitive sublime - Brown, Stephen Gilbert, 1949- (Albany : State University of New York Press, 2004)
Offers a psychocritical reading of Proust's À la recherche du temps perdu (Remembrance of Things Past).
Introduction : entering the garden -- The kiss of death : desire in the garden of good and evil -- The art of Sapphic desire : the curse of the little phrase -- The hymenoptera of self and other : the making and (un)making of knowledge -- Three moments of desire : the ideal, the real, and the remembered -- Recherche and the Rankian gaze -- Conclusion : the art of madness.
Includes bibliographical references (pages 237-240) and index.
Print version record.
English.
JSTOR
Keywords: Proust, Marcel, -- 1871-1922 -- Criticism and interpretation; Proust, Marcel, -- 1871-1922 -- Critique et interprétation.; Proust, Marcel, -- 1871-1922; Desire in literature; Désir dans la littérature.; LITERARY CRITICISM -- European -- French; Desire in literature; Criticism, interpretation, etc